Pengaruh Perceived Value dan Product Quality terhadap Repurchase Intention dengan Customer Satisfaction sebagai Variabel Intervening pada Pelanggan Fore Coffee di Semarang - Akmal Taufiiqul Hakim; Siti Sumiati (Lembaga Yasin AlSys, 2026)
The increasingly competitive modern coffee industry requires businesses not only to offer quality products but also to create customer value and satisfaction in order to foster repurchase intention. This study aims to analyze the influence of perceived value and product quality on repurchase intention, with customer satisfaction as an intervening variable, among Fore Coffee customers in Semarang. The research employed a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 100 respondents who had purchased Fore Coffee products in Semarang, selected using purposive sampling. Data analysis was conducted using SmartPLS 4 through descriptive statistics, outer model testing, and inner model evaluation. The results show that perceived value and product quality have a positive and significant effect on both customer satisfaction and repurchase intention. In addition, customer satisfaction has a positive and significant effect on repurchase intention. The findings further indicate that perceived value and product quality also influence repurchase intention indirectly through customer satisfaction. The study concludes that enhancing customers’ perceived value and maintaining consistent product quality can increase customer satisfaction and simultaneously strengthen repurchase intention. In practical terms, companies need to focus their strategies on reinforcing product quality and creating customer value to sustain consumer loyalty amid intensifying competition in the coffee industry.